Principles of diet therapy for sarcopenic obesity: A review - Е. V. Pavlovskaya; O. A. Kislyak; A. V. Starodubova (Терапевтический архив)
Nutrition and physical activity play a key role in the onset and progression of sarcopenic obesity (SO). Therefore, dietary interventions are essential in comprehensive programs to prevent and treat this condition. The classic approach to obesity diet therapy, which is to reduce the caloric value of the diet, is associated with a decrease in body weight due to both fat and fat-free components. In elderly patients with SO, a reduction in body weight impacts not only the muscle mass but also muscle function. A promising approach to diet therapy for this type of obesity is qualitative modification of the diet structure used for weight loss. The clinical role of specific components of diets, foods, and overall dietary patterns that are effective for CO treatment remains poorly understood. Sufficient intake of high-quality protein and branched-chain amino acids is known to stabilize and increase muscle mass, and recommended protein intakes in patients with SO of different ages continue to be discussed. It has been shown that in the elderly and senile age, the need for energy decreases; however, the need for protein increases. The role of ù-3 polyunsaturated fatty acids, vitamin D, calcium, and polyphenols in the treatment of SO may be due to their anti-inflammatory effect, as well as, possibly, activation of mitochondrial functions and regulation of myogenesis processes. Developing and using specialized foods containing proteins, branched-chain amino acids, and other key nutrients can improve the effectiveness of SO therapy. The review summarizes modern nutritional approaches to SO.